Entre la censura y el espéctaculo de la violencia: el reto Caravaggio en la fotografía - Castillo Archundia, Miguel Ángel (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
Photography from its origins has experienced the most variable uses, likewise the representation of violence. The photography is located between registration and subjectivity. This contributes to mistrust and criticism towards its use and its meaning. Criticism that has led to censor photography or to promote its ecology (appeal of the philosopher Susan Sontag in 1977 to take care of the meanings of the image). However, photography in its social use generates memory and makes realities visible. Photography, with the risk of capitalist appropriation and easy trivialization, must be carefully treated. This care is more urgent when dealing with photographs of the pain of others, according to Susan Sontag (2003). According to theater theoretician Ileana Diéguez (2016), the representations of the necroteatro (spectacular stagings of violently damaged bodies in public spaces with sobering intentions) have a dual function: they have the potential to serve for punitive purposes as well as to combat the punitive powers that generated them. Thus Diéguez proposes what she calls the “Caravaggio challenge” as a figure of counterhegemonic power where images of this violence are used against the perpetrators. Taking this into account, this work analyzes two images of necroteatro in the Mexican context: the photograph of Julio César Mondragón, dead and exhibited in 2014, and Susana Carrera, dead and exhibited in 2019. Both tortured and exhibited for sobering purposes. This work proposes the possibility of using certain images of violence in a political and ethical sense by placing them between the two extremes: the show and the concealment. This in Mexico, a country that has experienced increasing violence for a couple of decades and photographs of this violence are widely distributed and used for various purposes.

La fotografía desde sus orígenes ha experimentado los más variables usos. Así mismo la representación de la violencia en la misma. La fotografía está situada entre el registro y la subjetividad. Esto abona a la desconfianza y crítica en su uso como en su significación. Crítica que ha llevado a censurarla o promover su ecología (llamado a cuidar los significados de la imagen hecho por la filósofa Susan Sontag en 1977). Sin embargo, la fotografía en su uso social es generadora de memoria y visibiliza realidades. La fotografía, con el riesgo de la apropiación capitalista y fácil trivialización, debe tener tratamiento cuidadoso. Más apremiante es este cuidado cuando se tratan de fotografías del dolor de los demás, según Susan Sontag (2003). Según la teórica del teatro Ileana Diéguez (2016) las representaciones del necroteatro (montajes espectaculares de cuerpos violentados en espacios públicos con intenciones aleccionadores) son un doble dispositivo: tienen la potencialidad de servir para fines punitivos como para combatir a los poderes punitivos que generaron las violencias. Así Diéguez propone lo que llama el reto Caravaggio como una figura de poder contrahegemónico donde las imágenes de esta violencia se usan contra los perpetradores. En este trabajo se analizan dos imágenes del necroteatro del contexto mexicano: la fotografía de Julio César Mondragón, muerto y exhibido en 2014 y de Susana Carrera, muerta y exhibida en 2019. Ambxs torturadxs y exhibidxs con fines aleccionadores. Este trabajo propone la posibilidad del uso de determinadas imágenes de la violencia en un sentido político y ético, situándolas entre dos extremos: el espectáculo y el ocultamiento. Esto en México, un país que desde hace un par de décadas ha experimentado un aumento de violencia y donde las fotografías de la misma son ampliamente distribuidas como usadas con diversos fines.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2019-1815; Violencia; Necroteatro; Ética; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1638